Match-derived relative pitch area changes the physical and team tactical performance of elite soccer players in small-sided soccer games - Olthof, S. B. H.; Frencken, W. G. P.; Lemmink, K. A. P. M. (Journal of Sports Sciences, 2018)
Small-sided games (SSGs) are used in training sessions to prepare for full-sized matches. For the same number of players, smaller pitch sizes result in decreased physical performance and shorter interpersonal distances. A relative pitch area derived from the full-sized match results in larger pitch sizes and this may increase the fit between SSGs and full-sized matches. This study aimed to investigate SSGs with a traditional small pitch and a match-derived relative pitch area in youth elite soccer players. Four age categories (under-13, under-15, under-17 and under-19) played 4 vs. 4 plus goalkeepers on a small (40x30m, 120m2 relative pitch area) and large pitch (68x47m, 320m2 relative pitch area). The number of games per age category ranged 15-30. Positional data (LPM-system) were collected to determine physical (total distance covered, high intensity distance and number of sprints) and team tactical (inter-team distance, LPW-ratio, surface area, stretch indices, goalkeeper-defender distance) performance measures and tactical variability. On a large pitch, physical performance significantly increased, inter-team and intra-team distances were significantly larger and tactical variability of intra-team distance measures significantly increased. The match-derived relative pitch area is an important training manipulation and leads to changes in physical and tactical performance 4 vs. 4 plus goalkeepers.